Diseño de un plan de marketing para la empresa Alli Allpa ubicada en la provincia de Napo, para su línea de manejo sostenible de productos alternativos de madera de caña guadua - Cevallos Beltrán, Priscila Monserrath (2020)
Bamboo the industry of the future, today, this species originating from China and India grows naturally on all continents, except Europe and the poles is part of the grasses and has approximately 1500 species. In Ecuador, it is part of the cultural heritage with historical records from 10,000 years ago. There are 47 species of bamboo with 600000 hectares, which means 2 percent of the surface of the country, distributed in coast, sierra and east. The present research will be focused on the two species that are cultivated in the city of Napo: Giada Angustifolia and Dendrocalamus Aspar. The same ones that fulfill the characteristics to satisfy the needs of the construction market. Alli Allpa is an organization that seeks to generate an ecological-social productive chain, which is based on the economic development of the communities of the city of Napo, through the responsible cultivation of hectares of guadua cane and the environmental commitment that this represents for the sector. For what it wants to commercialize sheets, boards and planks of cane guadua focusing on the construction companies of the city of Quito. A survey and interviews have been carried out with 12 construction companies in the city of Quito in order to determine factors that guarantee the feasibility of the project that the organization wishes to carry out.